Astragalus and its formulas as a therapeutic option for fibrotic diseases: Pharmacology and mechanisms - Zhu, Yi; Chai, Yilu; Xiao, Guojin; Liu, Yufei; Xie, Xiaohong; Xiao, Wei; Zhou, Pengcheng; Ma, Wei; Zhang, Chuantao; Li, Liuying (Frontiers in Pharmacology, 2022)
Fibrosis is the abnormal deposition of extracellular matrix, characterized by accumulation of collagen and other extracellular matrix components, which causes organ dysfunction and even death. Despite advances in understanding fibrosis pathology and clinical management, there is no treatment for fibrosis that can prevent or reverse it, existing treatment options may lead to diarrhea, nausea, bleeding, anorexia, and liver toxicity. Thus, effective drugs are needed for fibrotic diseases. Traditional Chinese medicine has played a vital role in fibrotic diseases, accumulating evidence has demonstrated that Astragalus (Astragalus mongholicus Bunge) can attenuate multiple fibrotic diseases, which include liver fibrosis, pulmonary fibrosis, peritoneal fibrosis, renal fibrosis, cardiac fibrosis, and so on, mechanisms may be related to inhibition of epithelial-mesenchymal transition (EMT), reactive oxygen species (ROS), transforming growth factor beta 1 (TGF-β1)/Smads, apoptosis, inflammation pathways. The purpose of this review was to summarize the pharmacology and mechanisms of Astragalus in treating fibrotic diseases, the data reviewed demonstrates that Astragalus is a promising anti-fibrotic drug, its main anti-fibrotic components are Calycosin, Astragaloside IV, Astragalus polysaccharides and formononetin. We also review formulas that contain Astragalus with anti-fibrotic effects, in which Astragalus and Salvia miltiorrhiza Bunge, Astragalus and Angelica sinensis (Oliv.) Diels are the most commonly used combinations. We propose that combining active components into new formulations may be a promising way to develop new drugs for fibrosis. Besides, we expect Astragalus to be accepted as a clinically effective method of treating fibrosis.